Bertani dan Bergerak: Studi Strategi Mobilisasi Gerakan GAPOKTAN Desa Klampok di Probolinggo - Alfian Fajar (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2023)
This research discusses the social movement initiated by farmers in Klampok Village, Probolinggo Regency. Social movements are actions that have a shared value, which forms a group, which is based on the same goal. This movement consisted of farmers from Klampok Village who massively aspired to their demands to obtain underpasses in the process of building the Pasuruan-Probolinggo toll road. The movement was established due to farmers' dissatisfaction with various parties both from the government, the private sector, security apparatus and non- governmental organizations. This study uses the theory of resource mobilization which states that movement occurs due to the emergence of dissatisfaction from the community, so it is quite possible to bring up a social movement. The movement of the peasant movement has the following flow, targeting sympathizers, recruiting volunteers, activating networks, and motivating to participate. These steps were passed well, so that the movement is consistent and lasts for a long time and can have strong endurance. Farmers use the mobilization strategy so that it is effective in generating movement.